Analisis Pengaruh Pembelajaran Discovery terhadap Minat dan Hasil Belajar Asam Basa Peserta Didik - Sugiarti, Sugiarti; Herawati, Netti; Risdawati, Risdawati (Program Pasca Sarjana UNM, 2020)
This research is a quasi-experimental that aimed to find out the effect of discovery learning model toward interests and learning outcomes of students in class XI MIA SMAN 3 Pinrang. Independent variable in the research is discovery learning model and direct instruction and dependent variables is areinterest and learning outcomes of acid-base. The population in this research is all students class XI MIA SMAN 3 Pinrang that consist of six classes. Class XI MIA5 as an experiment group that consist of 31 students and class XI MIA2 as a control group that consist of 33 students. The result data of the research was obtained by interest questionnaires and learning outcomes test on acid-base topic for post test. Data were analysed using descriptive statistics and inferential statistics. The results of hypothesis testing for interest using t-test values obtained at tcount = 3,025 and significance level α = 0,05 with df = 3 and ttable = 1,66 because tcount > ttable it indscate that H0 failed. So the are is effect learning model effect learning model to learning interets of students class XI MIA SMAN 3 Pinrang. While for testing the learning outcomes using Mann-Whitney test obtained at Zcount = 3,48 and significance level α = 0,05 with df = 3 and ztable= 1,64. It shows that there is the effect of discovery learning model toward learning outcomes of students in class XI MIA SMAN 3 Pinrang. Testing correlation for experiment group is obtained rcount = 0,618 on significance level α = 0,05 and rtable = 0,355, so it can be concluded that there is positive correlation interests with learning outcomes in discovery learning model. While testing correlation for control group is obtained rcount = 0,488 on significance level α = 0,05 and rtable = 0,344, so it can be concluded that there is positive correlation interests and learning outcomes in direct instruction.